Special Bioactivities of Phenolics from Acacia dealbata L. with Potential for Dementia, Diabetes and Antimicrobial Treatments - Paula, Vanessa (2022)
Some diseases still need better therapeutic approaches, including the prevention of development. Natural resources are investigated with this purpose; among them, we decided to use an invasive plant as a main strategy. This will help in two ways: screening new compounds in flowers prevents the plant from causing widespread damage by controlling the dissemination and also obtains crude material for further applications. In the present study, flower extracts from Acacia dealbata Link harvested in Portugal were studied during three stages of flowering. Phenolic compounds were evaluated using HPLC/DAD and the total phenolics as the total flavonoids content was determined. The bioactivities screened were antioxidant potential, inhibitory activities of some enzymes (acetylcholinesterase, lipase and -glucosidase) and, to complete the screening, the inhibition of microbial growth was determined against Gram-negative and Gram-positive bacteria, as well as for yeasts. The data obtained suggested that the hydroethanolic extracts gave good results for all these biological activities and varied according to the maturation status of the flowers, with the early stage being the most active, which can be related to the chalcones content. This new approach will lead to the possible control of the invasive plant and also future perspective research for therapeutic purposes